Produkcja ciężarówek na początku XXI wieku: Chiny i Indie - największe wyzwania - Brach, Jarosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
At this moment the world market of middle weight and heavy trucks is dominated by only few -6-7 global makers that are mainly from Europe. Now for these producers the most important potential and challenging markets are Chinese and Indian ones. But the demand for the trucks originally produced by these potentates is limited in these countries by: low level of wages, low quality of services and the fact that generally, excluding highways, many roads are in bad condition. So in order to exist in China and India Volvo, IVECO or DaimlerChrysler have to collaborate (licensing, assembling) with domestic manufacturers. But in the coming future is expected that the level/degree of the market penetration achieved by these companies will rise hugely. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 37-51